What does data on functional income distribution tell us about trends in and correlates of income inequality in the Asia-Pacific? - Raihan, Selim (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper presents an analysis of the trend and patterns of the share of labour in GDP, the gap between wage and productivity, and inequality with a focus on Asia-Pacific countries for the period between 2004 and 2017. Descriptive analysis confirms a downward trend in labour income shares during the study period in most of the countries in the Asia-Pacific. Our analysis also shows that majority of the Asia-Pacific countries additionally witnessed a rise in the gap between labour productivity and wage, defined as the shortfall of wage from labour productivity as a percentage of wage. Furthermore, inequality, measured through the income Gini index also increased in these countries. Panel econometric regression results suggest that trade openness and FDI have a negative association with the labour share in GDP in the Asia-Pacific countries while being positively associated with the gap. Economic growth and structural transformation processes have also not been favourable in raising the labour share in GDP. Among other findings, technological development has not been labour-friendly in most of these countries. Non-agricultural employment share in total employment has a negative association with the labour share in GDP and is positively associated with the gap. Yet our analyses have confirmed that the reduction in labour share in income is associated with rising inequality in the Asia-Pacific countries. We conclude by discussing the role of two related major instruments of government policies -- revenue generation, and public expenditure on social sectors -- for addressing challenges related to widening inequality in the region.